Differential investment in visual and olfactory brain regions is linked to the sensory needs of a wasp social parasite and its host. Issue 4 (24th September 2021) - Rozanski, Allison N.; Cini, Alessandro; Lopreto, Taylor E.; Gandia, Kristine M.; Hauber, Mark E.; Cervo, Rita; Uy, Floria M. K.
Abstract: Obligate insect social parasites evolve traits to effectively locate and then exploit their hosts, whereas hosts have complex social behavioral repertoires, which include sensory recognition to reject potential conspecific intruders and heterospecific parasites. While social parasites and host behaviors have been studied extensively, less is known about how their sensory systems function to meet their specific selective pressures. Here, we compare investment in visual and olfactory brain regions in the paper wasp Polistes dominula, and its obligate social parasite P. sulcifer, to explore the links among sensory systems, brain and behavior. Our results show significant relative volumetric differences between these two closely related species, consistent with their very different life histories. Social parasites show proportionally larger optic lobes and central complex to likely navigate long‐distance migrations and unfamiliar landscapes to locate the specific species of hosts they usurp. Contrastingly, hosts have larger antennal lobes and calyces of the mushroom bodies compared with social parasites, as predicted by their sensory means to maintain social cohesion via olfactory signals, allocate colony tasks, forage, and recognize conspecific and heterospecific intruders. Our work suggests how this tradeoff between visual and olfactory brain regions may facilitate different sensory adaptations needed to perform social and foraging tasks by the host, including recognition of parasites, or to fly long distances and successful host localizing by the social parasite. Abstract : Brain reconstructions reveal differential investment in sensory brain regions between the obligate social parasite Polistes sulcifer and its host, P. dominula . Social parasites have larger optic lobes (blue), which reflects their visual needs to navigate long distances and locate a host nest. Contrastingly, hosts show large antennal lobes (yellow) and calyces of the mushroom bodies (red), coinciding with the olfactory and sensory processing needs of maintaining colony cohesion, including recognizing conspecific and heterospecific intruders. Scale = 1 mm.